CNS and CNS diseases in relation to their immune system - Xu, Jianhao; Ma, Canyu; Hua, Menglu; Li, Jiarui; Xiang, Ze; Wu, Jian (Frontiers in Immunology, 2022)
The central nervous system is the most important nervous system in vertebrates, which is responsible for transmitting information to the peripheral nervous system and controlling the body's activities. It mainly consists of the brain and spinal cord, which contains rich of neurons, the precision of the neural structures susceptible to damage from the outside world and from the internal factors of inflammation infection, leading to a series of central nervous system diseases, such as traumatic brain injury, nerve inflammation, etc., these diseases may cause irreversible damage on the central nervous or lead to subsequent chronic lesions. After disease or injury, the immune system of the central nervous system will play a role, releasing cytokines to recruit immune cells to enter, and the immune cells will differentiate according to the location and degree of the lesion, and become specific immune cells with different functions, recognize and phagocytose inflammatory factors, and repair the damaged neural structure. However, if the response of these immune cells is not suppressed, the overexpression of some genes can cause further damage to the central nervous system. There is a need to understand the molecular mechanisms by which these immune cells work, and this information may lead to immunotherapies that target certain diseases and avoid over-activation of immune cells. In this review, we summarized several immune cells that mainly play a role in the central nervous system and their roles, and also explained the response process of the immune system in the process of some common neurological diseases, which may provide new insights into the central nervous system.